General principles of law formed within the international legal system: Foggy or forgotten concept? - Đorđević-Aleksovski Sanja (Zbornik Radova Pravnog Fakulteta u Nišu)
The UN International Law Commission (ILC) has been codifying various sources of international law for decades. Thus far, its activities on the codification of general principles of law have resulted in three reports from the Special Rapporteur, where two categories of general principles of law have been identified in light of their different origins. The first category of general principles of law stem from municipal legal systems, while the second one stems from the international legal system itself. In the provisional conclusions adopted on the first reading in May 2023, the latter have been defined as "general principles of law that may be formed within the international legal system". The aim of this paper is to examine the controversial category of general principles of law. It has to be noted that there are conflicting views among scholars, members of the ILC itself and states regarding to general legal principles that may derive or may be formed within the framework of the international legal order. Hence, the paper will predominantly focus on these research questions: Do general principles of law formed within the international legal system have the potential to exist as an autonomous source of international law? Does the linguistic interpretation of Art. 38 paragraph 1 c) of the Statutes of both the Permanent Court of International Justice and the International Court of Justice (ICJ) support the arguments in favour of the standpoint that this category of principles has always been incorporated in the notion of general principles of law? The paper also focuses on the questions pertaining to the "recognition" of the general principles of law formed within the international legal order, and the subsequent question as to whether that amounts to consent of states.